HUBUNGAN BIG FIVE PERSONALITY DENGAN OCB PADA PNS GEN Y DI INSTANSI X - Kurniyadi Kurniyadi; Seta Aryawuri Wicaksana; Aisyah Pia Asrunputri (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
This study aims to determine the relationship between Big Five Personality with Organizational Citizenship Behavior (OCB). This research uses a quantitative research method with a correlational research type. The population in this research were 90 civil servants working at X Agency. Big Five Personality in this study was measured by the Big Five Inventory (BFI) and Organizational Citizenship Behavior (OCB) was measured by the Organizational Citizenship Behavior Scale (OCBS). Data analyzed by the Pearson Product Moment correlation. The results of this study showed that there is positive and significant correlation between agreeableness with OCB, there is positive and significant correlation between conscientiousness with OCB, there is positive and significant correlation between openness to experience with OCB, whereas neuroticism showed negative and significant correlation with OCB, but extraversion did not show significant correlation with OCB. The implication of this study is that organization can choose between training its employees to suit with the organizational culture or developing people management that suits with the character of its employees.